Performance improvement of hot stamping die for patchwork blank using mixed cooling channel designs with straight and conformal channels. (25th January 2020) - Yun, Sungho; Kwon, Junho; Cho, Wonhee; Lee, DongChan; Kim, Yongchan
Highlights: A mixed cooling channel (MCC) is proposed for patchwork blanks. Performance comparison between conventional channels and MCC is conducted. The optimum mass flow ratio in the MCC is determined to be 10%. The MCC exhibits higher cooling performance than conventional channels. The MCC exhibits a 5.8–9.0% greater daily production than conventional channels. Abstract: Although the cooling channel is a crucial factor for improving the performance of a hot stamping die, only a limited number of studies have been conducted concerning its design technology for patchwork blanks. In this study, a mixed cooling channel (MCC) is proposed to improve the cooling performance of the hot stamping die for patchwork blanks. The MCC is a combination of the straight cooling channel (SCC) and conformal cooling channel (CCC). The cooling capacity, average temperature, standard deviation, and figure of merit (FOM) of the SCC, CCC, and MCC are estimated by conducting three-dimensional transient thermo-fluid simulations. The optimum mass flow ratio of the MCC is determined to be 10% considering the cooling capacity, average temperature, and standard deviation. The MCC exhibits superior cooling performance to the SCC and CCC for all performance indicators because it effectively cools both the heat accumulated patch and the wide blank. In addition, the daily production of the MCC is 7.6–9.0% greater than that of the SCC, and 5.8–6.8% greater than that of the CCC.